Этикет на все случаи жизни - Чиненный А.И. Андрей Ильич (Гном-Пресс, 1998)
Экземпляры: аб. (1998) / Инвентарный номер: 40635 / Цена: / Сис.шифр: 87.717.7 / Авт.знак: Ч-63 / ГРНТИ: 02.51 / ББК: 87.717.7